Bidirectional negative relationship between thyrotropin and kidney function during alcohol intoxication in males - Unlu, Hayrunnisa; Yehia, Asmaa; Manji, Khalid; Manji, Noah; Treviño-Alvarez, Andrés M.; Cabeza De Baca, Tommy; Frye, Mark A.; Thomas, Leslie F.; Abulseoud, Osama A. (Frontiers in Nephrology, 2024)
IntroductionDespite a well-established direct toxic effect of alcohol on renal cells, there is a salutary dose-dependent effect of alcohol consumption on common laboratory parameters related to kidney performance. Alcohol also impacts thyroid hormones, while thyroid status modulates kidney function. The modulation of kidney parameters with thyrotropin (TSH) and thyroid status indicates a possible interaction between alcohol, kidney, and thyroid functions. This retrospective study was conducted to test the hypothesis that the positive effect of alcohol use on the estimated glomerular filtration rate (eGFR) is mediated by alcohol’s effect on thyroid hormones.MethodsWe reviewed the electronic medical records of 767 hospitalized adult patients free of thyroid disorders who received medical care in the Mayo Clinic Health System from June 2019 through June 2022 and had blood alcohol concentration (BAC), serum TSH, and serum creatinine measured during the hospitalization. We calculated the eGFR using both the re-expressed Modification of Diet in Renal Disease (MDRD II) study equation and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) Creatinine equation.ResultsWe found a significant relationship of BAC with eGFR (CKD-EPI) and TSH in males only. BAC had a positive association with eGFR (b = 0.24, p = 0.0001) and negative with TSH (b=-0.17, p = 0.006). The covariance between the two outcomes (eGFR and TSH) was negative (b = -0.12, p = 0.049). The path analyses using the eGFR MDRD II equation were not significant in males, whereas females had no significant path analyses with either of the eGFR equations.DiscussionWe observed that BAC influences both eGFR and TSH, whereas eGFR and TSH influence each other. After considering important covariates (e.g., age, body mass index, diabetes mellitus, cardiovascular disease, chronic kidney disease, and chronic liver disease) and the negative bidirectional effect of TSH and eGFR, a positive impact of BAC on eGFR was observed in males.